An evolutionarily conserved function of C-reactive protein is to prevent the formation of amyloid fibrils - Agrawal, Alok; Pathak, Asmita; Ngwa, Donald N.; Thirumalai, Avinash; Armstrong, Peter B.; Singh, Sanjay K. (Frontiers in Immunology, 2024)
C-reactive protein (CRP) binds to phosphocholine (PCh)-containing substances and subsequently activates the complement system to eliminate the ligand. The PCh-binding function of CRP has been conserved throughout evolution from arthropods to humans. Human CRP, in its structurally altered conformation at acidic pH, also binds to amyloid- (A) and prevents the formation of A fibrils. It is unknown whether the A-binding function of CRP has also been evolutionarily conserved. The aim of this study was to determine whether CRP isolated from American horseshoe crab Limulus polyphemus was also anti-amyloidogenic and whether this function required structural alteration of Limulus CRP (Li-CRP). Two CRP species Li-CRP-I and Li-CRP-II were purified from hemolymph by employing PCh-affinity chromatography and phosphoethanolamine-affinity chromatography, respectively. Both Li-CRP-I and Li-CRP-II bound to immobilized A at physiological pH. Unlike human CRP, Li-CRP did not require any changes in its overall structure to bind to A. Both Li-CRP-I and Li-CRP-II bound to A in the fluid phase also and prevented the fibrillation of A. Additionally, ion-exchange chromatography of purified Li-CRP indicated that a variety of Li-CRP molecules of different subunit compositions were present in Limulus hemolymph, raising the possibility that the presence of various Li-CRP species in hemolymph facilitates the recognition of a range of proteins with differing amyloidogenicity. We conclude that the binding of CRP to A is an ancient function of CRP. In invertebrates, the A-binding function of CRP can protect the host from toxicity caused by amyloidogenic and pathogenic proteins. In humans, the A-binding function of CRP can protect against inflammatory diseases in which the host proteins are ectopically deposited on either host cells or foreign cells in an inflammatory milieu since immobilized proteins may expose A-like structures after deposition at places where they are not supposed to be.